Evaluation of the Usage of Children’s Literature in Perpustakaan Alternatif Wilayah Selatan (PEVITA) Based on Circulation Study - Azhani, Hanik Aulia; Riani, Nur (UI Scholars Hub, 2026)
This study aims to evaluate the usage of children’s literature at the Southern Region Alternative Library (PEVITA) based on circulation data. This study focuses on users based on circulation data. It involves observing circulation data and conducting interviews with librarians and library users. The method used is a descriptive qualitative approach, where this study describes numerical data, such as the number of uses. Data collection techniques use semi-structured interviews, direct observation, and documentation. The results of this study show that first, the collection is evaluated based on user groups, classification numbers, year of publication, subjects and topics, and types of transactions. Second, collection usage based on user intensity: library users often spend approximately 2 hours in the library, user frequency: library users utilize 2 to 6 collections, collection dependency: library users are more dependent on the library location. There is a need to re-evaluate the points of subject and topic, borrowing transactions, and collection dependency. Recommendations for further research using a mixed method.